2021
DOI: 10.2147/jir.s313955
|View full text |Cite
|
Sign up to set email alerts
|

Biotite-Calx Based Traditional Indian Medicine Sahastraputi-Abhrak-Bhasma Prophylactically Mitigates Allergic Airway Inflammation in a Mouse Model of Asthma by Amending Cytokine Responses

Abstract: Purpose Asthma is a heterogeneous airway inflammatory disease with limited therapeutic options. Traditional medicine is extensively used for treating various ailments including asthma. Sahastraputi-Abhrak-Bhasma (SPAB) is a biotite-calx based Indian medicine. Methods We have tested for the anti-inflammatory and anti-asthmatic properties of SPAB, using a mouse model of ovalbumin-induced allergic asthma in-vivo and cell-based assays in-vitro. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Several studies have shown the association between TNF‐α (‐857 C/T) and autoimmune or inflammatory disorders 31 . However, the relationship between this polymorphism and OLP disease has not yet been investigated 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the association between TNF‐α (‐857 C/T) and autoimmune or inflammatory disorders 31 . However, the relationship between this polymorphism and OLP disease has not yet been investigated 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the association between TNF‐α (‐857 C/T) and autoimmune or inflammatory disorders. 31 However, the relationship between this polymorphism and OLP disease has not yet been investigated. 20 , 21 Limited studies with contradictory results have been done on other TNF‐α gene polymorphisms with inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Balakrishna et al. [ 8 ] showed dose-dependent increased immunomodulatory effects of Abhraka Bhasma .…”
Section: Discussionmentioning
confidence: 99%
“…It is also considered as rasayana and comprehensively used as a rejuvenator, aphrodisiac, anti-ageing and health promoter. There are evidence on hepatoprotective [ [4] , [5] , [6] ], anti-diuretic [ 7 ], anti-stress, anti-inflammatory and immunomodulatory [ 8 ], adaptogenic [ 9 ], memory-enhancing [ 10 ], anti-cancer [ 11 ], and anti-diabetic [ 3 ] role of Abhraka Bhasma .…”
Section: Introductionmentioning
confidence: 99%